The Structure and Culture of Negotiating Child Victims’ Rights in Cases of Sexual Violence - Mahfiana, Layyin; Masrukin, Masrukin; Zahro, Diana; Santoso, Lukman (Faculty of Law, University of Muhammadiyah Malang, 2026)
This article discusses the structure and culture of negotiating children's rights in sexual violence in Surakarta. This study employed a qualitative research method, collecting data through interviews and document analysis. The research writing was structured by data reduction, data presentation, and conclusions. Empirical and legal-philosophical approaches were applied to analyse the data, revealing significant weaknesses that require further attention. The lack of protection, justice, and recovery for child victims remains an issue, which hampers the functions of law enforcers, including the police, the prosecutor's office, and the judicial system. Justice in the system is procedural and formalistic in the context of the burden of proof, overlooking the best interests of the child and leaving child victims without justice and fair access to justice and restitution, while being burdened by procedural formalities. As studied, the majority of people in Surakarta are not fully aware of this matter. Stigmatisation lays the blame on the victims, while inadequate psychosocial support for child victims silences them. Without properly addressing these issues, many children experience discrimination and pressure that only hinders their recovery. This study concludes that to provide the necessary protection for child victims of violence and neglect, different sectoral responses need to be coordinated more effectively. Key recommendations include developing child-sensitive skills among law enforcement officials and other agencies, increasing public understanding of children's rights, simplifying regulations to eliminate duplication, and improving integrated, community-based victim services.